Al-Ḥisbah and Sharia Market Supervision: A Qualitative Study From Traders’ and Consumers’ Perspectives - Henry Martin Adriansyah; Mohd Winario (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2025)
This study examines the role of al-ḥisbah as a market supervisory institution from the perspectives of traders and consumers, addressing the limited empirical evidence on dual-actor perspectives in contemporary Sharia markets. It focuses on the functions of al-ḥisbah in ensuring transactional fairness, preventing fraudulent practices, and upholding Sharia principles in trading activities. Using a qualitative descriptive approach, data were collected through fieldwork at the Ulul Albab Sharia Market in Kampar Regency, Indonesia, involving in-depth interviews with five traders and five consumers, participatory observation, and documentation. Data analysis followed an interactive model comprising data reduction, data display, and conclusion drawing. The findings reveal that al-ḥisbah is perceived as a moral overseer and regulator of market ethics, playing a crucial role in fostering trust between traders and consumers. Traders associate its presence with fair competition and price transparency, while consumers perceive stronger protection against fraud and product quality manipulation. Nevertheless, the implementation of al-ḥisbah faces challenges related to limited human resources, insufficient socialization, and the need to adapt supervisory mechanisms to modern trade systems. This study underscores the importance of strengthening institutional capacity and integrating digital technologies into market supervision to enhance the effectiveness and sustainability of al-ḥisbah in the digital era.